2018
DOI: 10.2147/amep.s175395
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception, attitudes, and readiness toward online learning in dental education in Saudi Arabia: a cohort study

Abstract: PurposeThe purpose of this study was to assess students’ perception, attitudes, and readiness toward online dental education in Saudi Arabia.Materials and methodsThis is a longitudinal study using a 5-point Likert scale questionnaire distributed to a cohort group of undergraduate dental students at King Abdulaziz University, Faculty of Dentistry, Jeddah, Saudi Arabia, during their fourth year (T1) and internship year (T2). It assessed technological access, computer skills, online skills, and motivation level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 19 publications
12
94
1
3
Order By: Relevance
“…These are in contrast to the findings of study conducted by Linjawi among dental students in Saudi Arabia which indicated a high readiness level in computer skills among all the students who participated in the study. 10 In the present study 46.8% students listed flexible timings, ease of understanding and absence of monotony as the advantages of e-learning which is similar to findings of the study by Ogunnowo in Nigeria in which 45% of the participants agreed that e-learning assures schedule flexibility. 11 Also in the study done by Popovici and Mironov from Romania found that students were quite certain about the individualized feature of the e-learning but also about its collaborative character and a high-level of autonomy offered by e-learning.…”
Section: Discussionsupporting
confidence: 87%
“…These are in contrast to the findings of study conducted by Linjawi among dental students in Saudi Arabia which indicated a high readiness level in computer skills among all the students who participated in the study. 10 In the present study 46.8% students listed flexible timings, ease of understanding and absence of monotony as the advantages of e-learning which is similar to findings of the study by Ogunnowo in Nigeria in which 45% of the participants agreed that e-learning assures schedule flexibility. 11 Also in the study done by Popovici and Mironov from Romania found that students were quite certain about the individualized feature of the e-learning but also about its collaborative character and a high-level of autonomy offered by e-learning.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, demographic questions were added to better understand the population that completed the questionnaire. Accordingly, to design questionnaire items that had a reasonable level of reliability or validity, we based our items on related scales which have been published in the literature [13][14][15][16].…”
Section: Do Neurosurgeons Think That Virtual Neurosurgical Education mentioning
confidence: 99%
“…(19) The students in the present study reported very few technological difficulties, which can be considered as a positive factor as the success of any e-learning program depends on technological accessibility and the possession of a good Internet connection. (20) The students in the present study also reported no difficulties with the downloading and installation of the software or application or using of the application which can also be considered as a positive factor since students require technological skills like basic and advanced computer using skills, multimedia management skills, online management skills and time management skills to use any e-learning program. (20) As reported by Ghanizadeh et al, technical problems like poor connection are the most important limitation related to internet use among medical students.…”
Section: Discussion:-mentioning
confidence: 53%